Dehydration and nutrient loss during the haymaking process of tropical forage legumes - Arcanjo, Angelo Herbet Moreira; Araújo, Saulo Alberto do Carmo; Soares, Natalia Avila; Rocha, Norberto Silva; Neto Bellan, Júlio de Sales Lima [UNESP]; Ortêncio, Marluci Olício; Gomes, Fernanda de Kássia; Homem, Bruno Grossi Costa; da Silva, Edilane Aparecida; Evangelista, Antônio Ricardo (Wiley, 2024)
The objective was to evaluate nutrient loss during the dehydration process of three tropical forage legumes. The legumes studied were Stylosanthes spp. (80% Stylosanthes capitata + 20% Stylosanthes macrocephala), Pueraria phaseoloides, and Macrotyloma axillare. The forage was cut at 6:45 am, chopped and spread on polyethylene tarps to be exposed to the sun. Dry matter (DM) content, neutral detergent fiber corrected for ash and protein (NDFap), crude protein (CP), non-protein nitrogen (NPN), ether extract (EE), soluble carbohydrates (SCH), and total digestible nutrients (TDN) were analysed. On the third day, Stylosanthes spp. and Pueraria phaseoloides exhibited the highest dehydration rates (3.47% and 3.81% water loss/hour, respectively), followed by the first day (3.17% and 3.05% water loss/hour). There was an interaction (P < 0.05) between dehydration times and legumes for DM, CP, NPN, EE, and SCH. Among the legumes, Stylosanthes spp. had the highest (P < 0.05) NDFap levels (512.5 g.kg-1 in hay), Pueraria phaseoloides presented the highest (P < 0.05) CP levels, and Macrotyloma axillare exhibited the highest (P < 0.05) levels of EE and SCH (197.4, 25.7, and 32.2 g.kg-1 in hay, respectively). During dehydration, the contents of NPN, EE, and SCH decreased linearly (P < 0.05). All legumes showed a decrease in NPN, EE, and SCH contents.
Keywords: Fabaceae; hay; Macrotyloma axillare; Pueraria phaseoloides; Stylosanthes spp